Los principios del bioderecho europeo (2020)
One of the most important tasks of European Council was to engender responses to regulate different biomedical practices as they were arising and developing. Thus, the European Council regulated, for instance, the juridical status  of blood products as well as organs and tissues for transplantation and grafting, respectively. However, it was not easy to establish a European policy to foster a law armonized with new demands and challenges of biomedical advances, without a general juridical framework that would allow us to move forward into a communitarian regulation. In this scenario, the European Community sought to identify and define specific norms to recognize certain founding principles of European Biolaw, which should be understood as a law for establishing limits for scientific and biotechnological practices, and defining a human identity. This paper examines thoses principles and their utility for regulation as well as their contribution to consolidate biolaw as a discipline in Europe.